Image processing based automated solution for analysis of dimple fracture surfaces. (10th December 2020) - Banerjee, Siddhartha; Prabhakar, Chandesham; Chakraborti, Pravash Chandra; Saha, Sanjoy Kumar
Abstract: The present work aims to develop an automated solution for analysis of dimple tensile fracture surfaces. An image processing based technique has been proposed to extract the voids from the fractographic images of dimple fracture surfaces and also to analyse the void features. A two-stage process has been developed to extract the closed contour of the voids. At the first stage a global thresholding is followed by a sequence of processing, like thinning and morphological closing. In the second stage refinement process has been carried out on the large voids based on local characteristics. The proposed technique has been applied on the scanning electron fractographs of tensile fracture surfaces obtained by tensile testing of austenitic stainless steel at four different strain rates. It has been found that the size and density of extracted voids bear systematic relationship with tensile properties of the investigated steel. The average circular diameter with yield strength and tensile strength follows linear relationship. The number density of large voids is found to decrease with increase of strain rate and it also decreases with increase of average circular diameter in a linear manner. Similar nature of variation of tensile ductility has been observed both with strain rate and average circular diameter.